CROSS CULTURAL CONTEXTS IN ENGLISH LANGUAGE TEACHING - Mathew, Ingrid Brita (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2013)
This paper reflects on the need of students of English language to experience 'English-speaking culture'.  Due to the scarcity of natural contexts to communicate in English in West Sumatra it falls to English teachers to provide both English-speaking context and ongoing cross cultural analysis.  Some ways teachers across the curriculum can provide a context of English-speaking culture and implement cross cultural analysis while teaching are discussed.  The 'onion' model of culture is presented to show that culture is not only 'what' but also 'how' and 'why'.  Examples are given of how culture can be explicitly and implicitly taught. Key words/phrases: culture, context, English-speaking culture, cross cultural analysis